A web-based multi-agent system approach to document engineering. (14th February 2005) - Villar, Jose R.; Benavides, Carmen; Garcia, Isaias; Alonso, Angel; , Francisco Rodriguez
Document engineering is the automatic or semiautomatic process that assists a documental department of a company in the gathering, storing, retrieving and generation of articles and documents, and also in the distribution of these documents. A web-based multi-agent system was chosen as the best approach to build such a system, providing a flexible and scalable solution that not only automates but also improves the initial manual work. Several artificial intelligence techniques were studied and developed. This paper describes the solution designed, the text document classifier, the query subsystem, the automatic document generation subsystem and the web interfaces.